2007
DOI: 10.1590/s0101-20612007000200016
|View full text |Cite
|
Sign up to set email alerts
|

Alterações provocadas pela irradiação e armazenamento nos teores de ferro heme em carne de frango

Abstract: ResumoEstudos sobre o efeito da irradiação e do armazenamento em carnes de frango foram realizados para se conhecer melhor sua influência nos teores de ferro heme, não-heme, cor e pigmentos totais. Foram estudados coxa e filé de peito de frango. Estes foram irradiados a 0, 1 e 2 kGy e armazenados por 14 dias a 4 °C em câmara refrigerada. A determinação do conteúdo de heme e não-heme de carnes foi realizada através do método colorimétrico, empregando-se o reagente Ferrozine. Os valores de ferro heme foram influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…Color, tenderness, juiciness and overall acceptability had significantly (p<0.05) reduced with different storage time. Similar results were found by Souza et al (2007). Sweetie et al (2015) found that chicken, lamb and buffalo meat tenderization is increased with irradiation doses.…”
Section: Sensory Evaluationsupporting
confidence: 82%
“…Color, tenderness, juiciness and overall acceptability had significantly (p<0.05) reduced with different storage time. Similar results were found by Souza et al (2007). Sweetie et al (2015) found that chicken, lamb and buffalo meat tenderization is increased with irradiation doses.…”
Section: Sensory Evaluationsupporting
confidence: 82%
“…However, Kanatt et al (1997) did not find any change in sensory attributes such as appearance, color and odor after irradiating the chicken with 2.5 kGy. Similar reports were discussed by Souza et al (2007) who investigated the influence of radiation on the levels of iron and color of pigments of thighs and chicken breast meat irradiated at doses 0, 1 and 2.0 kGy and found that the color was not influenced by those doses. The lack of changes in sensory properties of the chicken meat was probably due to the low doses (below 3.0 kGy) used by these researchers.…”
Section: Ph Valuessupporting
confidence: 77%
“…Kim et al (2002) also found that the development of red color in irradiated meat was due to the production of gas, especially CO. Contradictory reports were found by Souza et al (2007) who investigated the influence of radiation on the levels of iron and color of pigments of thighs and chicken breast meat irradiated at doses 0, 1 and 2.0 kGy and found that color was not influenced by those doses. The present findings also were not in agreement with Al-Bachir et al (2010) who found that color of chicken kabab product were not influenced by the irradiation treatment.…”
Section: Sensory Evaluationmentioning
confidence: 96%